Implementasi gerakan literasi (gls) di SDN Glagah Yogyakarta - Anafiah, Siti; Anang Sudigdo; Juhana Binti Gusdur; Fenny Oktaviani Mansyur; Gusmao, Eufrasia Lopes (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this research is to determine 1) the implementation of the School Literacy Movement, 2) obstacles to implementing the School Literacy Movement, and 3) efforts to overcome obstacles to implementing the School Literacy Movement at SDN Glagah Yogyakarta. This research method uses a descriptive method with a qualitative approach. Setting The research was carried out at Glagah State Elementary School. The research objects are school principals, teachers and students. Research techniques use observation, interviews and documentation. Data analysis uses data reduction, data description presentation, and conclusions. The results of this research indicate that SDN Glagah has implemented GLS activities in a planned manner. The implementation of GLS is reflected in the habit of students to love reading and creating works. GLS activities at SDN Glagah are supported by many parties, including school members, parents, the community and related agencies.